PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG, DAN PERPUTARAN PERSEDIAAN TERHADAP LIKUIDITAS PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Marnida Rajagukguk; Erni Setiawati; Mansyur (OBOR: Oikonomia Borneo, 2019)
Abstract - This study aims to analyze and determine the effect of cash turnover, accounts receivable turnover, and inventory turnover on liquidity in food and beverage companies listed on the Indonesia stock exchange. The results of this study indicate that cash turnover and accounts receivable turnover have a significant effect on liquidity in food and beverage companies listed on the Indonesia stock exchange, while inventory turnover has no significant effect on liquidity on food and beverage companies listed on the Indonesia stock exchange.